ANALISIS PENGARUH PEMAHAMAN STANDAR AKUNTANSI PEMERINTAHAN, PENDIDIKAN-LATIHAN (DIKLAT), DAN PENGALAMAN KERJA TERHADAP KINERJA PENYUSUN LAPORAN KEUANGAN PEMERINTAH DAERAH - Harlina, Puji Rahayu; Fachruzzaman, Fachruzzaman; Baihaqi, Baihaqi (JURNAL FAIRNESS, 2013)
This study examined the effect of understanding the Government Accounting Standards, Education-training, and on the performance of work experience in the financial report's authors Unit (SKPD) Bengkulu provincial government. The study was a descriptive survey method. Data were obtained on the apparatus authors employee financial statements on all SKPD in Bengkulu province government. Data obtained using a questionnaire given to the respondents directly. Data were analyzed using SPSS. Based on data from 40 respondents who participated in the study, the research found that simultaneous understanding of the Government Accounting Standards, Education-training, and work experience affect the performance of the compilers of the financial statements on regional work units (SKPD) Bengkulu provincial government. Only a partial understanding of the Governmental Accounting Standards, and work experience has a significant positive impact on the performance of the compilers of the financial statements on education government of Bengkulu province.